The Involvement of Athletes with Intellectual Disability in Community Sports Clubs - Florian Pochstein; Gemma Diaz Garolera; Sabine Menke; Roy McConkey (Disabilities, 2023)
People with intellectual disability lack opportunities to engage in sports, although the benefits of doing so may be even greater for them. One option is to encourage their inclusion in mainstream sports clubs that exist in nearly all European communities. Although there is a growing knowledge base within organisations such as Special Olympics in adjusting sports to meet the needs of people with intellectual disability, inclusion in community clubs raises additional challenges. This exploratory study aimed to garner the experiences of coaches alongside those of clubs members—with and without disabilities—in 12 community sports clubs in three European countries. In all 20 coaches and 51 members took part in semi-structured interviews. A thematic content analysis was used to devise a conceptual model describing an inclusive sports club. The overarching theme was that inclusive clubs require an ongoing balancing between a focus on sporting skills and performance, with managing the needs and characteristics of the players and the inter-relationships among them. Six subthemes were identified that described the core strategies to the effective functioning of the clubs. However, the vision and commitment of coaches was crucial and their recruitment was the main challenge the clubs faced. In addition, new opportunities for training coaches are needed to support the extension of inclusive clubs across a range of sports and locations. Continuing research could usefully identify the benefits to club members and identify sport-specific adaptations required to make clubs more fully inclusive.